Fisetin regulates the biological effects of rat nucleus pulposus mesenchymal stem cells under oxidative stress by sirtuin‐1 pathway - Qing Zhou; Chao Zhu; Anwu Xuan; Junyou Zhang; Zhenbiao Zhu; Liang Tang; Dike Ruan (Immunity, Inflammation and Disease)
Abstract Background Excessive oxidative stress has been accepted as one of the critical factors for intervertebral disc degeneration (IDD), which is associated with low back pain (LBP). Fisetin (Fis) is a bioactive flavonoid that possesses strong bioactive activity. In present study, we aimed to illuminate the role of Fis on nucleus pulposus mesenchymal stem cells (NPMSCs). Methods NPMSCs were isolated and cultured from rat NP tissues and identified by flow cytometry and multilinear differentiation. The cytotoxicity of Fis, EX‐527, and hydrogen peroxide (H2O2) on NPMSCs was validated using Cell Counting Kit‐8 tests. Cell apoptosis was tested by flow cytometry and TUNEL assay. Inflammatory mediators were assessed by Elisa tests, RT‐PCR. Extracellular matrix (ECM) metabolism was measured by Western blot analysis and RT‐qPCR. The expression of the SIRT1 was evaluated by Western blot analysis. Results NPMSCs were successfully isolated and cultured from rat NP tissues, and it has been identified by flow cytometry and multilinear differentiation. The results showed that Fis attenuated H2O2‐induced apoptosis, inflammation, and ECM degradation of NPMSCs. Moreover, the above protective effects of Fis can be inhibited by EX‐527, a unique SIRT1 inhibitor, indicating that SIRT1 may involve in the mechanism of Fis in protecting NPMSCs from oxidative stress. Conclusions As a natural compound with little cytotoxicity on NPMSCs, Fis alleviate H2O2‐induced apoptosis, inflammation, and ECM degradation by suppressing oxidative stress, this finding may add the theoretical basis for research on new treatment of IDD based on NPMSCs.